Experiential learning in management education - Eckhaus, Eyal; Klein, Galit; Kantor, Jeffrey (Business, Management and Economics Engineering, 2017)
Management studies have been criticized for lagging behind the actual needs of organizations, ignoring experiential dimensions. We address this issue by applying experiential learning theory using an accountancy-oriented board game designed to help participants learn about cost management. The game was played in a pricing course with an enrolment of 104 accountancy students. We examined the impact levels of game entertainment and comprehensibility on the course material comprehension as well as the game’s impact on the final grade in the course. Results show that game participants had significantly higher grades than students that did not participate in the game, and that entertainment and comprehensibility of the game predict the understanding of course material. We also found that managerial employment capability can be predicted by level of challenge participants derive from the game. This study addresses the gap between traditional management education and practice. It provides empirical evidence of the value of hands-on gameplay experience for assimilation of course concepts and strategies. The results confirmed the importance of exposing players through an entertaining game simulation to challenges that arise in the business world. In addition, we lay the ground for future studies on the novel usage of the game as a tool to assess management skills.